Enhanced Recovery of Phenolic and Tocopherolic Compounds from Walnut (Juglans Regia L.) Male Flowers Based on Process Optimization of Ultrasonic Assisted-Extraction: Phytochemical Profile and Biological Activities - Anca Pop; Ionel Fizeșan; Laurian Vlase; Marius Emil Rusu; Julien Cherfan; Mihai Babota; Ana-Maria Gheldiu; Ioan Tomuta; Daniela-Saveta Popa (MDPI AG, 2021)
The extraction of bioactive compounds present in walnut (Juglans regia L.) male flowers (WMFs) was performed based on an experimental design using ultrasonic-assisted extraction. Solvent nature, extraction time, and water content were selected as experimental variables, and phenolic, flavonoidic, and condensed tannins contents and antioxidant properties were evaluated. Acetone was the solvent with the highest extraction performance, with the extracts obtained using this solvent displaying an increased concentration of bioactive compounds and increased antioxidant activities. For several extracts with high bioactive content, individual polyphenolic and tocopherolic compounds were evaluated by means of LC-MS and LC-MS/MS. The best extraction conditions for polyphenolic (2.86 mg gallic acid equivalents/g WMF) and tocopherolic compounds (29.4 µg/g WMF) were acetone with 40% water content (N20) and acetone with 20% water content (N15), respectively. Although the total tocopherol concentrations were lower than in other Juglans regia parts, most of the total tocopherol quantity was provided by the highly biologically active δ-tocopherol (84%). Significant quantities of quercetin (101.9 µg/g), hyperoside (2662.9 µg/g), quercitrin (405.7 µg/g), and isoquercitrin (1293.7 µg/g) were determined in WMF (N20). Both extracts inhibited the enzymatic activity of α-glucosidase and tyrosinase; however, an increased inhibition was observed for N20, the extract with the higher polyphenolic content. Conversely, N15 had higher anticancerous activity on the cell lines used, with a moderate selectivity towards the cancerous phenotype being observed for both extracts. At non-cytotoxic concentrations, both extracts displayed good antioxidant activities in cellular cultures, decreasing basal and H2O2-induced oxidative stress. This is the first characterization of both hydrophilic and lipophilic phytochemicals in WMF extracts. The outcomes of our study reveal that walnut male flowers have strong biological activities, thus justifying further research to demonstrate their usefulness in the food, pharmaceutical, and/or cosmetic industries.